Shopaholic & baby - Kinsella, Sophie (Black Swan, 2007)
Becky's life is blooming! She's working at London's newest fashion store The Look, house-hunting with husband Luke (her secret wish is a Shoe Room)... and she's pregnant! She couldn't be more overjoyed - especially since discovering that shopping cures morning sickness. Everything has got to be perfect for her baby: from the designer nursery...to the latest, coolest pram...to the celebrity, must-have obstetrician. But when the celebrity obstetrician turns out to be her husband Luke's glamorous, intellectual ex-girlfriend, Becky's perfect world starts to crumble.